1938
DOI: 10.1139/cjr38d-009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Precooling and Rate of Freezing on the Quality of Dressed Poultry

Abstract: The rate at which poultry is frozen has been shown to have no effect on the number of bacteria present, and little, if any, effect on the extent of surface desiccation or development of visceral taint. The development of taint appears to depend primarily on the period during which the product is held at temperatures above the freezing point, and little advantage is gained by freezing promptly after slaughter, since taint development occurs during thawing.A quantitative study of the amount of fluid exuded (drip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1939
1939
1999
1999

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…on volume of drip loss has been observed previously with beef (Empey, 1933)) dressed poultry, and minced chicken meat (Sair and Cook, 1938). Amino acids and peptides and certain nucleotides have been shown to contribute to taste and mouth satisfaction (Kazeniac, 1961) ; the loss of these materials in drip may therefore affect the flavor of slow frozen poultry more than of fast frozen poultry.…”
Section: Taste Panel Analysesmentioning
confidence: 75%
“…on volume of drip loss has been observed previously with beef (Empey, 1933)) dressed poultry, and minced chicken meat (Sair and Cook, 1938). Amino acids and peptides and certain nucleotides have been shown to contribute to taste and mouth satisfaction (Kazeniac, 1961) ; the loss of these materials in drip may therefore affect the flavor of slow frozen poultry more than of fast frozen poultry.…”
Section: Taste Panel Analysesmentioning
confidence: 75%
“…Freezing has long been known to increase the amount of drip (Koonz and Ramsbottom, 1939). According to Sair and Cook (1938) increases in drip after freezing are not readily detectable with the whole carcass but are influenced by the removal of skin, cutting of meat, and particularly mincing. Baker et al (1976) studied drip and cooking loss of broilers subjected to multiple freezing and thawing and suggested that although freezing increases drip there is less of a loss during cooking so that total loss remains relatively constant.…”
Section: Discussionmentioning
confidence: 98%
“…He found that the least drip came from muscle tissue having a p H vahe of 6.3 or higher. Sair and Cook (1938) found that the maximum drip-occurred at a pH of 5.2, decreasing to no drip at pH 6.4. Also the time elapsing between slaughter and freezing was a factor-the longer the aging period the less was, the drip.…”
Section: Review Of Literaturementioning
confidence: 95%